Diapriidae e Ismaridae (Hymenoptera, Diaprioidea) de áreas de Mata Atlântica do estado de São Paulo - Comério, Emerson Fraga [UNESP] (2014)
Diapriidae (Hymenoptera, Diaprioidea) is cosmopolitan, with three subfamilies, 194 genera and 2080 described species. Diapriinae, Belytinae and Ambositrinae occur in the Neotropics. Belytinae and Ambositrinae parasitize immature Mycetophilidae and Sciaridae (Diptera) and Diapriinae parasitize mostly Diptera, with some species associated to ants. Ismaridae is cosmopolitan, with only one genus, Ismarus Haliday, with 32 species, of which 12 related to the Neotropics and two of them to Brazil; are secondary parasitoid larvae of Dryinidae (Hymenoptera). This research aimed to study the Diapriidae Ismaridae and five conservation areas of the Atlantic Forest of State of São Paulo. Samples were collected monthy between Octuber 2009 and March 2011 at Parque Estadual Intervales (Ribeirão Grande) and Estação Ecológica Juréia-Itatins (Iguape); between November 2009 and December 2010 at Parque Estadual da Serra do Mar-Núcleo Picinguaba (Ubatuba); between November 2009 and August 2011 at Núcleo Santa Virgínia (São Luiz do Paraitinga) and December 2009 and February 2011 at Parque Estadual Morro do Diabo (Teodoro Sampaio). In each área were installed five Malaise traps, distant 50 meters apart and active throughout entire the period. The biological material was sent to the Laboratório de Sistemática e Bioecologia de Parasitoides e Predadores of the Agência Paulista de Tecnologia dos Agronegócios (APTA), in Ribeirão Preto, State of São Paulo where identified the subfamilies and genera. Specimens of Szelenyiopria Fabritius, Ismarus and Propsilomma (Ashmead) were identified in species. Specimens of Szelenyiopria and Ismarus belonging to Coleção de Hymenoptera da Universidade Federal do Espírito Santo were included in this study. Were collected 11.464 specimens of Diapriidae, of three subfamilies: Belytinae (9.833 exemplars/85.8% the total collected), Diapriinae (1.603/14.0%) and Ambositrinae ...